Embriologi Manusia dalam Perspektif al-Qur'an dan Sains: Kajian Integratif Ayat-Ayat Penciptaan - Afud Ahmad Fudholi (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2026)
This research aims to examine the concept of embryology as explained in the Qur'an and relate it to modern scientific discoveries in the field of biology. The approach used is library research with thematic interpretation analysis of Qur'anic verses that discuss the process of human creation, particularly the stages of fetal development in the womb. The findings indicate that the Qur'anic explanation of embryology has a strong correlation with modern scientific theories, both in terminology and the described biological stages. The Qur'an explicitly mentions several important stages, such as nuthfah, 'alaqah, mudhghah, to the formation of bones and their covering with flesh, which correspond to the embryogenesis process known in science. This research also emphasizes the importance of integrating science and religion in education, particularly in biology learning, so that students gain a holistic understanding, encompassing both physical and spiritual aspects of human creation.